Contaminant removal from manufactured fine aggregates by dry rare-earth magnetic separation. (November 2017) - Miceli, Hayla; Rossi, Mateus G.; Neumann, Reiner; Tavares, Luís Marcelo
Graphical abstract: Highlights: Samples of manufactured fine aggregates from three gneiss rocks were collected. High-intensity dry magnetic separation was used to remove deleterious components of the fine aggregates. 77–78% yield with good rejection of biotite, hornblende, kaolinite, chlorite and montmorillonite was reached. Abstract: Manufactured fine aggregates have become a viable alternative to natural sands in construction and building all over the world, in particular where a sustainable source of the later is not available. Technologies that are now associated to processing these materials include vertical shaft impact crushing and dry classification, which have the direct ability to improve particle shape and control the amount of filler material, respectively. Granites and gneisses are among the rocks that are most commonly used for aggregate production worldwide. While composition generally creates no major issues in their application as coarse aggregates, the use of these rocks in production of manufactured sand can represent a challenge, mostly associated to the presence of appreciable amounts of contaminating minerals, in particular micas, which can have a negative impact on both rheology and strength of mortars and concrete. The present work demonstrates the improvement in the characteristics of three manufactured fine aggregates through dry rare-earth magnetic separation. It demonstrates that the mica/biotite content has been reduced significantly, leading also to a significant improvement in shape in the product. Magnetic separation has been found to have the added advantage of removing other deleterious minerals also present in these rocks, thus improving the brightness (given the dark coloration of mafic minerals removed) and potentially the performance of such fine aggregate in mortars, concrete and asphalt.